Evaluation of Grapevines for Resistance to Downy Mildew (Plasmopara viticola) under Laboratory and Field Conditions - Prajongjai, T.; Poolsawat, O.; Pornbungkerd, P.; Wongkaew, S.; Tantasawat, P.A. (South African Journal of Enology and Viticulture, 2016)
Downy mildew of grapevine (Vitis vinifera L.), caused by the oomycete Plasmopara viticola, can seriously devastate grapevine production in tropical countries, such as Thailand. Four susceptible grapevine cultivars, four potentially resistant lines and 18 F1 hybrids, propagated by air layering and chip budding, were evaluated for resistance to downy mildew at laboratory (using a detached leaf assay) and field (natural infection in 2011 and 2013) levels. Significant differences in the disease scores among grapevine genotypes, ranging from 0.54 (resistant) to 4.83 (susceptible) and 3.30 (resistant) to 7.70 (susceptible), were observed under the laboratory and field conditions respectively. No significant difference in disease severity was observed between the two propagation methods or between the two different years of field evaluations. Resistance evaluations under both conditions consistently classified ‘NY88.0517.01’ and ‘NY65.0550.04’ as resistant lines what would be useful as parents for future breeding programmes. Moreover, one F1 hybrid, ‘SUT0403.09’, was reported to have considerable resistance to downy mildew under both laboratory and field conditions for the first time. The field resistance level of this hybrid was almost comparable to its highly resistant parent ‘Wilcox 321’, suggesting its potential for the future development of resistant cultivars in Thailand. Although the ranking of genotypes varied between screening methods, the resistance levels of the 26 grapevine genotypes evaluated under laboratory and field conditions were comparable based on the Spearman’s rank correlation coefficients of 0.73 (p ≤ 0.01). These results suggest that the laboratory screening assay is efficient for the rapid, reliable and economical identification of resistant hybrids in grapevine breeding programmes.